New foundations for knowledge in educational administration, policy, and politics : science and sensationalism - Mitchell, Douglas E. (Lawrence Erlbaum Associates, Publishers, 2020)
The relationship between academic social scientists and educational policymakers : a brief historical overview /|rMargaret A. Nash --|tThe evolution of educational administration : the Daniel E. Griffiths' legacy /|rDouglas E. Mitchell and Flora Ida Ortiz --|tTruth or consequences? : reflections on the theory movement and its aftermath in education /|rBrian Rowan --|tLegal inquiry and equal opportunity /|rPaul Green --|tScholarship in educational administration : at a crossroads or dead end? /|rRonald H. Heck --|tScientific research and moral leadership in schools /|rGail C. Furman --|tThe changing landscape in school governance : implications for establishing claims /|rKenneth K. Wong --|tThe science and politics of urban education leadership : toward a reorienting narrative /|rDorothy Shipps --|tSensational science : generating valid and reliable knowledge of educational administration, policy, and politics /|rDouglas E. Mitchell --|tCoherent knowledge and confident professional practice /|rDouglas E. Mitchell.